1996
DOI: 10.1128/jb.178.4.1018-1029.1996
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated methane monooxygenase from Methylococcus capsulatus (Bath)

Abstract: An active preparation of the membrane-associated methane monooxygenase (pMMO) from Methylococcus capsulatus Bath was isolated by ion-exchange and hydrophobic interaction chromatography using dodecyl ␤-D-maltoside as the detergent. The active preparation consisted of three major polypeptides with molecular masses of 47,000, 27,000, and 25,000 Da. Two of the three polypeptides (those with molecular masses of 47,000 and 27,000 Da) were identified as the polypeptides induced when cells expressing the soluble MMO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
394
4
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 270 publications
(425 citation statements)
references
References 57 publications
24
394
4
3
Order By: Relevance
“…Earlier workers have used [ 14 C]-labeled HCCH as the mechanism probe of the catalytic site and have detected the radioactivity primarily in the "~27 kDa" subunit in denaturing SDS-PAGE gels of the protein [8,18]. In the latter work [8], the labeling experiment is not clean, leading to the observation of [ 14 C]-radioactivity in the protein band corresponding to the PmoB subunit as well as other cytoplasmic proteins ( Figure 3 of ref 18) Subsequently, the "~27 kDa" subunit was assigned to PmoA by N-terminal sequencing [8].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier workers have used [ 14 C]-labeled HCCH as the mechanism probe of the catalytic site and have detected the radioactivity primarily in the "~27 kDa" subunit in denaturing SDS-PAGE gels of the protein [8,18]. In the latter work [8], the labeling experiment is not clean, leading to the observation of [ 14 C]-radioactivity in the protein band corresponding to the PmoB subunit as well as other cytoplasmic proteins ( Figure 3 of ref 18) Subsequently, the "~27 kDa" subunit was assigned to PmoA by N-terminal sequencing [8].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, HCCH is considered to be a mechanism-based probe of the enzyme catalytic site. Earlier experiments on cell extracts [18], whole cells [8], and the purified pMMO [8] using [ 14 C]-labeled HCCH as the substrate have shown that only the "~27 kDa" protein band on SDS-PAGE gels [18] is labeled with radioactivity, and N-terminal sequencing was used to assign this protein band to the PmoA subunit [8]. This observation suggests that the catalytic site of the enzyme resides within the…”
Section: Scheme 1 X-ray Crystal Structure Of the Cu 3 -Pmmo Of Methymentioning
confidence: 99%
See 3 more Smart Citations